Comparison of metamizole and paracetamol effects on colonic anastomosis and fibroblast activities in Wistar rats - Eko Purnomo; Dwi Aris Agung Nugrahaningsih; Nunik Agustriani; Gunadi (BMC, 2020)
Abstract Background Leakage following colorectal anastomosis surgery causes various complications associated with high morbidity and mortality, especially in pediatric patients. It might be caused by the use of non-steroidal anti-inflammatory drugs (NSAIDs) as postoperative analgesics. This study aimed to compare the effect of metamizole and paracetamol on colonic anastomosis and fibroblast activities, including proliferation, migration, and collagen synthesis, in Wistar rats. Methods Rats were divided into control, paracetamol and metamizole groups. The colonic anastomosis was evaluated by determining the integrity of the muscle layers, the formation of granulation tissue, and mucosal anastomosis. Fibroblast activities were analyzed by measuring the proliferation, migration, and collagen synthesis. Results Metamizole caused more damage to muscle layer integrity, more inhibition of granulation tissue formation in the anastomosis area and lower mucosal anastomosis compared with paracetamol and control groups. Metamizole had a higher cytotoxic effect than paracetamol, which suppressed the proliferation and migration of fibroblasts. Furthermore, both drugs did not affect the synthesis of collagen. Conclusion Metamizole shows worse effects on the integrity of muscle layers, inhibition of granulation tissue formation, mucosal anastomosis, fibroblast proliferation, and migration, but not collagen synthesis, than paracetamol in Wistar rat intestines following colonic anastomosis. These findings might indicate that paracetamol is safer than metamizole as analgesic following colonic anastomosis.